A Unified Approach to Phytosiderophore Natural Products. Issue 2 (28th October 2020) - Kratena, Nicolas; Gökler, Tobias; Maltrovsky, Lara; Oburger, Eva; Stanetty, Christian
Abstract: This work reports on the concise total synthesis of eight natural products of the mugineic acid and avenic acid families (phytosiderophores). An innovative „east‐to‐west" assembly of the trimeric products resulted in a high degree of divergence enabling the formation of the final products in just 10 or 11 steps each with a minimum of overall synthetic effort. Chiral pool starting materials (l ‐malic acid, threonines) were employed for the outer building blocks while the middle building blocks were accessed by diastereo‐ and enantioselective methods. A highlight of this work consists in the straightforward preparation of epimeric hydroxyazetidine amino acids, useful building blocks on their own, enabling the first synthesis of 3''‐hydroxymugineic acid and 3''‐hydroxy‐2'‐deoxymugineic acid. Abstract : Phytosiderophores are natural products enabling plants to absorb essential metal ions from the soil. Until now only specific solutions towards particular phytosiderophores had been reported. In this work, the entire family of these compounds is made synthetically accessible by using a divergent synthetic strategy.